2016
DOI: 10.1016/j.rppede.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interaction with clowns on vital signs and non-verbal communication of hospitalized children

Abstract: Objective:Compare the non-verbal communication of children before and during interaction with clowns and compare their vital signs before and after this interaction.Methods:Uncontrolled, intervention, cross-sectional, quantitative study with children admitted to a public university hospital. The intervention was performed by medical students dressed as clowns and included magic tricks, juggling, singing with the children, making soap bubbles and comedic performances. The intervention time was 20min. Vital sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
1
8
0
8
Order By: Relevance
“…29,30 It has been demonstrated that undergoing a humorous experience can reduce the discomfort generated by pain 31 and increase the patient' s response threshold 32 in both adults and children. 33 Clown interventions improve mood, evidenced by nonverbal communication, 34 decrease pain, 34,35 and increase clinical improvement. 35 Furthermore, clown interventions diminish preoperative anxiety in children undergoing penile surgery and lead to a shortening of the overall hospital stay time, thereby reducing the overall medical costs.…”
mentioning
confidence: 99%
“…29,30 It has been demonstrated that undergoing a humorous experience can reduce the discomfort generated by pain 31 and increase the patient' s response threshold 32 in both adults and children. 33 Clown interventions improve mood, evidenced by nonverbal communication, 34 decrease pain, 34,35 and increase clinical improvement. 35 Furthermore, clown interventions diminish preoperative anxiety in children undergoing penile surgery and lead to a shortening of the overall hospital stay time, thereby reducing the overall medical costs.…”
mentioning
confidence: 99%
“…The positive effect of family social support is on adjusting for events in a stressful life (Bordone, Arpino, & Aassve, 2017). Support from the family can improve ways of dealing with problems or solve problems focused on reducing stress reactions through the attention, information and feedback needed (Alcântara et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A interação lúdica com palhaços é uma estratégia eficiente de redirecionamento da energia para sentimentos positivos e benéficos (ALCANTÂRA, 2016). Nesse contexto, o tato e o contato com esses momentos demonstram claramente uma melhora do quadro clínico sem a necessidade de comprovação estatística para visualizar a "mágica" do palhaço.…”
Section: Discussionunclassified